Evaluasi Program Pendidikan dan Pelatihan Kepemimpinan Tingkat IV Pemerintah Provinsi Nusa Tenggara Barat - Muslihin, Muslihin (JTP - Jurnal Teknologi Pendidikan, 2017)
The purpose of this research is to explain the program implementation qualityand efectivity of the leadership training and education of forth level of the Government of West Nusa Tenggara Province. This research includes evaluation research program with Kirkpatrick’s model (reaction, learning, behaviour, result) by using descriptive qualitative approach. Data collection instruments used were interview, observation guidelines, the study documents, and questionnaires. Data analysis using models Miles and Huberman through the display of data, data reduction, and data verification. The results showed that the participants’ reactions to learning by training trainers in the category adequate with a score of 76.67%, reaction training participants towards learning lectures by speakers that are in adequate category with a score of 75.17%, according to the coach’s ability participants with a score of 82.93 %, both in terms of system management and operational administration by 70.62%. Participants’ reactions to the energy aspects of training and education that is equal to 79.03%. The effectiveness of the program in terms of the reaction of participants was on the score of 65.52 or the adequate category and questionnaire results 91.67% of participants consider the information given during the training is less practical nature. Keywords: Program evaluation, Kirkpatrick model, leadership, training and education Tujuan penelitian ini adalah untuk menjelaskan kualitas dan efektivitas penyelenggaraan Diklat Kepemimpinan Tingkat IV pada Pemerintah Provinsi NTB. Penelitian ini termasuk jenis penelitian evaluasi program dengan model Kirkpatrick (reaction, learning, beaviour, result) dengan menggunakan pendekatan kualitatif deskriptif. Instrumen pengumpulan data yang digunakan adalah pedoman wawancara, pedoman observasi, studi dokumen, dan kuesioner. Analisis data mengunakan model Miles dan Huberman melalui display data, reduksi data, dan verifikasi data. Hasil penelitian menunjukkan bahwa reaksi peserta diklat terhadap pembelajaran oleh widyaiswara berada pada kategori memadai dengan skor 76,67 %, reaksi peserta diklat terhadap pembelajaran ceramah oleh narasumber berada pada kategori memadai dengan skor 75,17 %, kemampuan coach menurut peserta dengan skor 82,93 %, sistem pengelolaan baik dari segi administrasi dan operasional sebesar 70,62 %. Reaksi peserta terhadap aspek tenaga kediklatan yaitu sebesar 79,03%. Efektivitas program dari segi reaksi peserta adalah pada skor 65,52 atau pada kategori memadai dan hasil kuesioner 91,67% peserta menganggap pengetahuan yang diberikan selama diklat kurang bersifat praktis. Kata kunci: Evaluasi program, model kirkpatrik, kepemimpinan, pendidikan dan pelatihan